A World Without Hunger Josué de Castro and the History of Geography - Davies, Archie (Liverpool Latin American Studies, 2022)
An Open Access edition of this book is available on the Liverpool University Press website and the OAPEN library as part of the Opening the Future project with COPIM. Drawing on the rich personal archive of the geographer Josué de Castro, this book tells a new history of geography by following one of the twentieth century's most influential and creative Brazilian intellectuals from the estuarine city of Recife to the halls of the UN, the chambers of Brasília, and exile amid the political fervour of the universities of Paris in 1968. This is the first English language book on the absorbing life of Josué de Castro. It follows modern anticolonial geographical thought in formation, re-reading Castro's metabolic, humanist geography as the anchor of a utopian practice of freedom: the demand for a world without hunger. Starting from Castro's life and work, the book offers new takes on the history of nutrition, translation in geography, Brazilian modernist art and practice in post-war internationalism, the radical geographical intellectual, the problem of the region in the Brazilian Northeast, and the birth of political ecology and critical environmental thought. At once a biographical intellectual history and a work of geographical theory, this innovative book tells the story of 20th century geography from a new angle and in new company.